2016 IEEE 55th Conference on Decision and Control (CDC) 2016
DOI: 10.1109/cdc.2016.7799410
|View full text |Cite
|
Sign up to set email alerts
|

On the benefits of surrogate Lagrangians in optimal control and planning algorithms

Abstract: Abstract-This paper explores the relationship between numerical integrators and optimal control algorithms. Specifically, the performance of the differential dynamical programming (DDP) algorithm is examined when a variational integrator and a newly proposed surrogate variational integrator are used to propagate and linearize system dynamics. Surrogate variational integrators, derived from backward error analysis, achieve higher levels of accuracy while maintaining the same integration complexity as nominal va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Further theoretical studies of the symplectic filtering approach can be performed by backwards error analysis [7] applied to the state-adjoint system. We also note that recent work [18] has shown that it may be possible to construct arbitrarily high-order variational integrators that are still linearizable one-step maps. These integrators are developed through backward error analysis [7] by constructing surrogate Lagrangians.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Further theoretical studies of the symplectic filtering approach can be performed by backwards error analysis [7] applied to the state-adjoint system. We also note that recent work [18] has shown that it may be possible to construct arbitrarily high-order variational integrators that are still linearizable one-step maps. These integrators are developed through backward error analysis [7] by constructing surrogate Lagrangians.…”
Section: Resultsmentioning
confidence: 83%
“…The term L d ðq k ; q kþ1 ; hÞ is referred to as the discrete Lagrangian, and f À k ; f þ k are the left and right discrete forces, respectively [6]. Taking variations of the discrete 1 In the conclusion of this document we mention some recent work [18] that describes the generation arbitrary-order VIs that are still one-step maps. These VIs may provide another choice of integrator that satisfies the aforementioned requirements while also yielding a higher order method.…”
Section: Variational Integratorsmentioning
confidence: 99%
“…We have illustrated the construction of modified Lagrangians and the possible issue of parasitic solutions with examples. Our construction is potentially useful to create more accurate variational integrators, for example in the spirit of [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…This follows by Legendre transformation from the well-known fact that modified equations for symplectic integrators are Hamiltonian. The construction of a modified Lagrangian was combined in [2,3] with the idea of modifying integrators [1] to construct variational integrators of improved convergence order.…”
Section: Introductionmentioning
confidence: 99%